Morphological and functional outcomes of operatively treated Achilles tendon ruptures. Issue 3 (2nd July 2020) - Nicholson, Gareth; Walker, Josh; Dawson, Zoe; Bissas, Athanassios; Harris, Nick
ABSTRACT: Objectives : Achilles tendon rupture leads to functional impairments and these may be underpinned by morphological changes in the muscle-tendon unit. The functional performance of the injured limb will be impaired regardless of time since surgery and these impairments occur alongside changes in muscle-tendon morphology. Methods : Following operative treatment of Achilles tendon rupture and short-term immobilization, 12 patients completed a battery of tests during a single visit to the laboratory (performed an average of 4.4 ± 2.6 years post-surgery). Patients completed the Achilles' tendon rupture score (ATRS), tests of the ankle and hip range of motion (ROM) and ultrasound measurements of muscle-tendon architecture. Data on isokinetic (30°/s, 60°/s) plantar flexion strength, jumping performance and walking-running were also collected on the same visit. Percentage deficits were expressed relative to the non-injured limb and determined for statistical significance (p < 0.05). Relationships between outcome measures and time since surgery were tested using Pearson's correlation coefficients (p < 0.05). Results : The repaired limb showed a shorter muscle fascicle length (12.1–19.6%), increased fascicle pennation (18.0 ± 22.14%) and reduced muscle thickness (9.1–20.1%) in the gastrocnemius and/or soleus along with greater tendon cross-sectional area (46.7 ± 34.47%). Functionally, the repaired limb displayed lower countermovement jump height (−12.6 ± 15.68%) and longer drop jump contact times (5.5 ± 5.7%). Also, the repaired limb showed reduced hip internal-external ROM (6.3 ± 8.2%) but no differences existed between limbs for plantar flexion ROM and strength or gait characteristics. Good ATRS outcomes were reported (mean: 87.9 ± 16.2, range: 43–100) which related to time since surgery (r = 0.79) but individual ATRS items did not correlate with corresponding objective measures. Conclusion : Plantar flexor atrophy following surgically treated Achilles tendon rupture is partially compensated for by remodeling of the fascicles; however, impairments may still persist many years into the postoperative period although these may be more pronounced in high-velocity activities.